MicroRNA-375 suppresses esophageal cancer cell growth and invasion by repressing metadherin expression - Hu, Changmei (Oncol Lett, 2017)
Accumulating evidence indicates that aberrant expression of microRNAs is involved in tumorigenesis, tumor progression and response to therapy. MicroRNA-375 (miR-375) is an important cancer-associated RNA that is downregulated in multiple types of cancer. In the present study, the potential effects of and underlying molecular mechanism for miR-375 in esophageal cancer were investigated. The expression of miR-375 in paired esophageal squamous cell carcinoma (ESCC) and non-tumor tissues from 10 patients was quantified using the reverse transcription-quantitative polymerase chain reaction. The miR-375 levels in the ESCC cell line EC109 and a normal esophageal epithelial cell line, Het-1A, were also detected. The effect of miR-375 on ESCC cell growth and invasion was determined using Cell Counting kit-8, flow cytometry and invasion assays. A luciferase assay was conducted for target identification. The results of the present study revealed that miR-375 was downregulated in ESCC tumor tissue and EC109 cells compared with normal tissue and Het-1A cells (P<0.01). Overexpression of miR-375 inhibited EC109 cell growth and invasion, and induced cell cycle arrest. In addition, metadherin (MTDH) was demonstrated to be a direct target of miR-375 (P<0.01). The overexpression of miR-375 downregulated MTDH (P<0.01), cyclin D1 (P<0.05) and vascular endothelial growth factor (P<0.01) expression, while upregulating epithelial cadherin (P<0.01) expression, which may account for its effect on ESCC cell proliferation and invasion. The results of the present study suggest that the miR-375/MTDH axis represents a target for the treatment of ESCC.